2021
DOI: 10.1177/21501327211036251
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Good COVID-19 Preventive Behaviors Among Older Adults in Urban Communities in Thailand

Abstract: Introduction/Objectives: The coronavirus disease 2019 (COVID-19) pandemic has affected mobility and mortality entire age, especially older adults. The COVID-19 preventive behaviors among older adults during the pandemic should be determined. To our knowledge, little is known about the preventive behavior during the COVID-19 pandemic among older adults living in urban areas in Thailand and the factors predicted to their behavior. Hence, the present study aimed to assess COVID-19 preventive behaviors among older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
39
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 54 publications
12
39
0
2
Order By: Relevance
“…6 COVID-19 prevention behaviors were extremely important in reducing viral spread and casualties in populations at risk. 7 As COVID-19 is transmitted by droplets, 8 health authorities in several countries, including Thailand, promoted frequent hand washing with soap and water, use of masks, and social distancing to reduce exposure, in addition to strict citywide lockdowns to control the spreads of the epidemic. 9 Moreover, accessing fundamental health information, obtaining a genuine understanding of the principles of disease prevention, and managing public health remained crucial, especially for at-risk populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 COVID-19 prevention behaviors were extremely important in reducing viral spread and casualties in populations at risk. 7 As COVID-19 is transmitted by droplets, 8 health authorities in several countries, including Thailand, promoted frequent hand washing with soap and water, use of masks, and social distancing to reduce exposure, in addition to strict citywide lockdowns to control the spreads of the epidemic. 9 Moreover, accessing fundamental health information, obtaining a genuine understanding of the principles of disease prevention, and managing public health remained crucial, especially for at-risk populations.…”
Section: Introductionmentioning
confidence: 99%
“… 6 ) COVID-19 prevention behaviors were extremely important in reducing viral spread and casualties in populations at risk. 7 )…”
Section: Introductionmentioning
confidence: 99%
“…2,21,23) Contrary to previous findings, patient age was not associated with HL in older adults in urban communities in Thailand. 14,24) The current study's findings indicated that HL was associated with positive self-care behaviors, whereas self-care behaviors were negatively associated with blood sugar levels. Thus, increasing HL in patients with diabetes results in improved self-care behavior and, as a result, lower blood sugar levels.…”
Section: Discussionmentioning
confidence: 54%
“… 2 , 21 , 23 ) Contrary to previous findings, patient age was not associated with HL in older adults in urban communities in Thailand. 14 , 24 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation